Robotic natural orifice specimen extraction surgery (NOSES) for anterior resection - Toan Duc Pham; Tomas Larach; Bushra Othman; Amrish Rajkomar; Alexander G. Heriot; Satish K. Warrier; Philip Smart (Annals of Coloproctology, 2023)
Minimally invasive colorectal surgery is currently well-accepted, with open techniques being reserved for very difficult cases. Laparoscopic colectomy has been proven to have lower mortality, complication, and ostomy rates; a shorter median length of stay; and lower overall costs when compared to its open counterpart. This trend is seen in both benign and malignant indications. Natural orifice specimen extraction surgery (NOSES) in colorectal surgery was first described in the early 1990s. Three recent meta-analyses comparing transabdominal extraction against NOSES concluded that NOSES was superior in terms of overall postoperative complications, recovery of gastrointestinal function, postoperative pain, aesthetics, and hospital stay. However, NOSES was associated with a longer operative time. Herein, we present our technique of robotic NOSES anterior resection using the da Vinci Xi platform in diverticular disease and sigmoid colon cancers.